2020
DOI: 10.1021/acs.chemrestox.0c00216
|View full text |Cite
|
Sign up to set email alerts
|

Partial Blockade of Human Voltage-Dependent Sodium Channels by the Marine Toxins Azaspiracids

Abstract: Azaspiracid toxins were first identified at the end of the last century in Irish mussels, and during the last two decades considerable cytotoxic and neurotoxic effects caused by these toxins have been described. Azaspiracids are synthesized by dinoflagellates and accumulate in several species of filter-feeding bivalve mollusks, thereby incorporating into the food chain and causing human intoxications. Among the cellular effects of azaspiracids, inhibition of spikes in neurons and hyperpolarization of the neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…VRAC channels were initially proposed to be related with the neurotoxic effects of azaspiracids, because the toxic effect of these compounds in neurons was diminished in the presence of nonspecific chloride channel blockers . In addition to this initial observation, recently we demonstrated that long-term exposure of the cells to azaspiracids led to a dramatic cell shrinkage and to evident changes in cell morphology under light microscopy . Because, apart from osmotically challenging the cells, the only known chemical activator of the VRAC channels is the GTPγS (guanosine 5′- O -[gamma-thio]­triphosphate) which needs to be used at concentrations of about 100 μM and it is capable of activating VRAC channels when applied into the intracellular solution, we engaged in the complete pharmacological characterization of the potential role of azaspiracids in VRAC activation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…VRAC channels were initially proposed to be related with the neurotoxic effects of azaspiracids, because the toxic effect of these compounds in neurons was diminished in the presence of nonspecific chloride channel blockers . In addition to this initial observation, recently we demonstrated that long-term exposure of the cells to azaspiracids led to a dramatic cell shrinkage and to evident changes in cell morphology under light microscopy . Because, apart from osmotically challenging the cells, the only known chemical activator of the VRAC channels is the GTPγS (guanosine 5′- O -[gamma-thio]­triphosphate) which needs to be used at concentrations of about 100 μM and it is capable of activating VRAC channels when applied into the intracellular solution, we engaged in the complete pharmacological characterization of the potential role of azaspiracids in VRAC activation.…”
Section: Discussionmentioning
confidence: 93%
“…Despite the fact that ion channels were suggested to underlie some of the cellular alterations caused by this group of toxins, only few studies have been released on this subject. ,, In this sense, initial studies reported that AZA1 inhibited electrical activity in spinal cord neurons, and recently, it was demonstrated that AZA1 and AZA2 at nanomolar concentrations acted as partial blockers of voltage-gated sodium channels (Na v ). However, the blockade of sodium channels was not related with the cellular modifications elicited by azaspiracid, because low nanomolar (nM) concentrations of TTX (a selective channel blocker) did not modify the effect of AZA on cell adhesion …”
Section: Introductionmentioning
confidence: 99%
“…A variety of studies have reported alteration in several pathways under AZAs treatment both in vitro and in vivo. Some of the features determined in vitro comprise cytoskeletal reorganization, apoptosis induction, and mitochondrial and nuclear impairment [ 16 , 210 , 211 ], depending on dose, experimental time, and cell line. Interestingly, AZAs effects on ion channels have also been described.…”
Section: Mechanism Of Action and Toxicity: The Need For Predefined To...mentioning
confidence: 99%
“…Research pointed that these phycotoxins at micromolar concentrations decreased potassium currents acting as open state blockers of ether-à-go-go potassium channel (hERG) [ 212 ]. In the same line, three VGSCs isoforms are partially blocked in vitro by AZA1, AZA2, and AZA3 [ 211 ]. A recent publication reported the interaction of azaspiracids with volume-regulated anion channels (VRAC).…”
Section: Mechanism Of Action and Toxicity: The Need For Predefined To...mentioning
confidence: 99%
See 1 more Smart Citation